+0

# Help. ​

0
30
3
+1380

Help.

NotSoSmart  Jan 11, 2018
Sort:

#1
+5888
0

x + y   =   3     subtract  x  from both sides to get     y  =  3 - x

x2 + y2   =   9       Substitute  3 - x  for  y  in this equation.

x2 + (3 - x)2   =   9               Now we can solve this for  x .

x2 + (3 - x)(3 - x)   =   9

x2 + 9 - 6x + x2   =   9          Subtract  9  from both sides and combine like terms.

2x2 - 6x   =   0                      Factor  x  out of both terms on the left side.

x(2x - 6)   =   0                     Set each factor equal to zero.

x  =  0          or          2x - 6  =  0

x  =  3

Now we can use these values for  x  to find  y .

If   x = 0 ,     0 + y = 3    so    y = 3

If   x = 3 ,     3 + y = 3    so    y = 0

The solutions are   (0, 3)   and   (3, 0) .

hectictar  Jan 11, 2018
#2
+5888
+1

y  =  (x - 2)(x - 3)(x + 3)

The zeros of this are the  x  values that make  y  be zero, that is, the  x  values when

0  =  (x - 2)(x - 3)(x + 3)

Set each factor equal to zero and solve each for  x  .

x  - 2  =  0     so     x  =  2

x  - 3  =  0     so     x  =  3

x + 3  =  0     so     x  =  -3

The zeros are  2, 3, -3

hectictar  Jan 11, 2018
#3
+80874
+1

Thanks, hectictar.....I messed that first one up earlier...!!!

CPhill  Jan 11, 2018
edited by CPhill  Jan 11, 2018

### 16 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details